Arbitraje y múltiples contratos - Cantuarias Salaverry, Fernando (2017)
The globalized world demands increasingly complex contractual operations. In that context, businesses have implemented multiple related contracts with the aim of achieving a common goal.In this paper, the authors analyze the complex situation of the arbitration regarding multiple contracts. Through the review of relevant case-law, the various solutions that characterize arbitration between multiple contracts are described. Finally, the authors address the overlap of non-signatory parties in the context of multiple contracts.